Selective Denervation of the Facial Dermato-Muscular Complex in the Rat: Experimental Model and Anatomical Basis - Tereshenko, Vlad; Dotzauer, Dominik C.; Maierhofer, Udo; Festin, Christopher; Luft, Matthias; Laengle, Gregor; Politikou, Olga; Klein, Holger J.; Blumer, Roland; Aszmann, Oskar C.; Bergmeister, Konstantin D. (Frontiers in Neuroanatomy, 2021)
The facial dermato-muscular system consists of highly specialized muscles tightly adhering to the overlaying skin and thus form a complex morphological conglomerate. This is the anatomical and functional basis for versatile facial expressions, which are essential for human social interaction. The neural innervation of the facial skin and muscles occurs via branches of the trigeminal and facial nerves. These are also the most commonly pathologically affected cranial nerves, often requiring surgical treatment. Hence, experimental models for researching these nerves and their pathologies are highly relevant to study pathophysiology and nerve regeneration. Experimental models for the distinctive investigation of the complex afferent and efferent interplay within facial structures are scarce. In this study, we established a robust surgical model for distinctive exploration of facial structures after complete elimination of afferent or efferent innervation in the rat. Animals were allocated into two groups according to the surgical procedure. In the first group, the facial nerve and in the second all distal cutaneous branches of the trigeminal nerve were transected unilaterally. All animals survived and no higher burden was caused by the procedures. Whisker pad movements were documented with video recordings 4 weeks after surgery and showed successful denervation. Whole-mount immunofluorescent staining of facial muscles was performed to visualize the innervation pattern of the neuromuscular junctions. Comprehensive quantitative analysis revealed large differences in afferent axon counts in the cutaneous branches of the trigeminal nerve. Axon number was the highest in the infraorbital nerve (28625±2519), followed by the supraorbital nerve (2131±413), the mental nerve (3062±341) and the cutaneous branch of the mylohyoid nerve (343±78). Overall, this surgical model is robust and reliable for distinctive surgical deafferentation or deafferentation of the face. It may be used for investigating cortical plasticity, the neurobiological mechanisms behind various clinically relevant conditions like facial paralysis or trigeminal neuralgia as well as local anesthesia in the face and oral cavity.